The Development of An Automated Module Performance Tracker Output Dashboard - Mohd Sabri, Mohd Nazri; Angeleta Radakrishnan, (Jurnal Kejuruteraan, Teknologi and Sains Sosial (JKTSS), 2024)
Planning the production process is crucial for any industry. A production plan outlines how production will be carried out. An industry's management and manufacturing team must prepare and search for solutions for any production line downtime that may occur. The production team is capable of making contributions that go beyond simply spending hours moving data around. It might take a lot of time and effort to pull out a manual report, and disengaged workers can result in low production and high employee turnover. Developing an effective module performance tracker output data for an automated dashboard can save a lot of time and energy. This paper discusses and analyses the effectiveness of automating manual spreadsheet reports through a time study conducted at XYZ company. An automated dashboard not only saves 59.11% of time but also gives the management team visibility of all the important information.